2013
DOI: 10.1016/j.jana.2013.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Address HIV and Intimate Partner Violence in Sub-Saharan Africa: A Review of the Literature

Abstract: HIV and intimate partner violence (IPV) are commonly co-occurring epidemics affecting the health of women globally and especially in sub-Saharan Africa. There is a need for interventions that address both HIV and IPV in health care settings. Our review examined recent literature for intervention studies that explored both HIV and IPV. Of the 9 interventions identified, only 2 were set in health care settings; the remainder were community based. Large multifaceted community-based interventions showed promise in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 34 publications
1
32
0
Order By: Relevance
“…A recent systematic review of 44 best-evidence HIV prevention interventions identified by the CDC found only five interventions that addressed IPV. 38 Another review of HIV interventions that address IPV in sub-Saharan Africa 45 identified three effective interventions that resulted in increasing condom use and HIV testing, and/or decreasing sexual partners. 4648 No interventions included in these systematic reviews significantly reduced any type of IPV and none focused exclusively on women or girls who use drugs.…”
Section: Resultsmentioning
confidence: 99%
“…A recent systematic review of 44 best-evidence HIV prevention interventions identified by the CDC found only five interventions that addressed IPV. 38 Another review of HIV interventions that address IPV in sub-Saharan Africa 45 identified three effective interventions that resulted in increasing condom use and HIV testing, and/or decreasing sexual partners. 4648 No interventions included in these systematic reviews significantly reduced any type of IPV and none focused exclusively on women or girls who use drugs.…”
Section: Resultsmentioning
confidence: 99%
“…In a survey of sexually active low-income Black and Hispanic adult men age 18–35 years, 41% reported IPV perpetration in the past year (Santana, Raj, Decker, La Marche, & Silverman, 2006). These data underscore the enormous need for programs and interventions that address partner violence and associated mental health comorbidities (Anderson, Campbell, & Farley, 2013; Bair-Merritt et al, 2014; Black, 2011; Campbell et al, 2008). …”
Section: Discussionmentioning
confidence: 97%
“…Intervention studies among HIV-uninfected individuals have also received attention. Among the trauma-informed HIV primary prevention intervention literature, two recent reviews of interventions in sub-Saharan Africa have nicely summarized this body of intervention research [20, 21]. Combined, they reported on the efficacy of over a dozen prevention interventions addressing the intersection of violence and HIV, predominately focused on youth and women in sub-Saharan Africa, with studies employing various intervention approaches including community-wide, school-based, and individual-level behavioral strategies to address violence and decrease HIV sexual risk behaviors.…”
Section: Introductionmentioning
confidence: 99%